2018
DOI: 10.1002/jctb.5657
|View full text |Cite
|
Sign up to set email alerts
|

The Bi/Bi2WO6 heterojunction with stable interface contact and enhanced visible‐light photocatalytic activity for phenol and Cr(VI) removal

Abstract: BACKGROUND Semiconductor photocatalysis is the most promising green and energy‐saving technology for environmental remediation. Unfortunately, photocatalysis nanotechnology for its practical application is often challenged by the low capturing ability for visible light and use of expensive noble metals. In this work, we report the non‐noble Bi nanoparticles assembled on Bi2WO6 with enhanced visible‐light photocatalytic activity for decontamination of phenol and hexavalent chromium in water. RESULTS The 3% Bi/B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…For BISB, the diffraction peaks were widened, indicating that smaller particles and fragments were present in the product. Beside the peaks that could be attributed to the BiOI and Bi 2 S 3 structure, a weak peak at 27.17° could be assigned to hexagonal metallic Bi (ICSD: 44-1246), ,, which indicated that BiOI, Bi 2 S 3 , and Bi coexisted in the BISB sample. The formation of metallic Bi nanoparticles might be due to the reductive nature of EtOH and MA at high temperatures …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For BISB, the diffraction peaks were widened, indicating that smaller particles and fragments were present in the product. Beside the peaks that could be attributed to the BiOI and Bi 2 S 3 structure, a weak peak at 27.17° could be assigned to hexagonal metallic Bi (ICSD: 44-1246), ,, which indicated that BiOI, Bi 2 S 3 , and Bi coexisted in the BISB sample. The formation of metallic Bi nanoparticles might be due to the reductive nature of EtOH and MA at high temperatures …”
Section: Resultsmentioning
confidence: 97%
“…The condition of the surface elements was important for the performance of a photocatalyst, and these were further characterized via XPS. , As shown in Figure S1, Bi, I, O, and C were present in all of the samples. The magnified XPS analysis in Figure illustrated that the binding energies around 618.7 and 630.2 eV could be assigned to the characteristic of I 3d 5/2 and I 3d 3/2 of I – , indicating the presence of I – at the surface of all three samples. ,, In the O 1s region between 156–168 eV, overlapping peaks were observed; after multipeak fitting, three groups of peaks could be determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the effect of the heterostructure on the charge transfer resistance was also investigated, and EIS measurements were carried out to characterize the asprepared samples. It is well-accepted that the smaller arc diameter in Nyquist plots implies a lower resistance of the interfacial charge transfer in the electrode-electrolyte interface region on the surface of the electrode [49]. 3.7.…”
Section: Resultsmentioning
confidence: 99%
“…[ 91 ] Jia et al fabricated Bi/Bi 2 WO 6 composites via two‐step route. [ 92 ] First, flower‐like Bi 2 WO 6 microspheres were fabricated through solvothermal process. Subsequently, Bi nanoparticles were anchored on the Bi 2 WO 6 microspheres by a second solvothermal reaction route.…”
Section: Strategies For Enhancing Photocatalytic Activity Of Metallic Bi‐based Photocatalystsmentioning
confidence: 99%